Getting Off the List: Leadership, Learning, and Context in Two Rural, High-Needs Schools. Issue 1 (January 2020) - Klar, Hans W.; Moyi, Peter; Ylimaki, Rose M.; Hardie, Suzy; Andreoli, Parker M.; Dou, Jingtong; Harrington, Keneisha; Roper, Cindy; Buskey, Frederick C.
In this article, we report findings from two cases of rural, high-needs elementary schools in the Southeastern United States that successfully improved learning outcomes for their students. As illustrated by our findings, a combination of effective teacher professional development, focused student learning initiatives, and enhanced community and family involvement contributed to the removal of the schools from priority and below average designations. In addition to illustrating the leadership practices that positively influenced improvement efforts in these two schools, and expanding the nascent body of scholarship on context-responsive leadership, our findings serve as a starting point for a larger project centered on the nexus of school leader agency in increasingly diverse cultural contexts.